2014
DOI: 10.1002/dmrr.2502
|View full text |Cite
|
Sign up to set email alerts
|

Safety of saxagliptin: events of special interest in 9156 patients with type 2 diabetes mellitus

Abstract: Pooled data from 20 studies confirm that saxagliptin has a favourable safety and benefit-risk profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 52 publications
2
38
1
2
Order By: Relevance
“…The discrepancy is further supported by the difference between the findings in this trial and the results of a post hoc pooled analysis of 20 phase 2 and 3 trials (n = 9,156) comparing saxagliptin with placebo or active comparator, which found an increased risk for fractures with saxagliptin treatment (HR 1.81 [95% CI 1.04-3.28]) (30). The patient population in the pooled analysis was younger; had a shorter duration of diabetes, better renal function, and less concomitant medication; and was generally healthier compared with the SAVOR TIMI-53 patient population.…”
Section: The Incretin System and Bone Metabolismmentioning
confidence: 61%
“…The discrepancy is further supported by the difference between the findings in this trial and the results of a post hoc pooled analysis of 20 phase 2 and 3 trials (n = 9,156) comparing saxagliptin with placebo or active comparator, which found an increased risk for fractures with saxagliptin treatment (HR 1.81 [95% CI 1.04-3.28]) (30). The patient population in the pooled analysis was younger; had a shorter duration of diabetes, better renal function, and less concomitant medication; and was generally healthier compared with the SAVOR TIMI-53 patient population.…”
Section: The Incretin System and Bone Metabolismmentioning
confidence: 61%
“…Two meta-analyses suggested that the DPP-4 inhibitors are associated with reduced CV risk (23,24). Importantly, however, these data were obtained predominantly from relatively small and/or short-term investigations (18,19,30), systematic reviews (21,28,29), and pooled analyses (20,22,(25)(26)(27)31,32) in by-and-large younger and healthier study participants with very limited, and generally unadjudicated, CV safety information.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no evident association between the application of saxagliptin and the incidence of gastrointestinal adverse events, infections, hypersensitivity, pancreatitis, skin lesions, lymphopenia, thrombocytopenia, hypoglycaemia, bone fracture, severe cutaneous adverse reactions, opportunistic infection, angioedema, malignancy, and worsening renal function, the patients still need to be cautious to initiate the saxagliptin treatment. 154 For example, hypersensitivity-related urticaria and facial oedema in the 5-study pooled analysis up to week 24 were reported in 1.5%, 1.5%, and 0.4% of patients who received saxagliptin 2.5 mg, saxagliptin 5 mg, and placebo, respectively, though none of these events in patients who received saxagliptin required hospitalization or were reported as a life-threatening event. 155,156 Notably, the concern about the possible association between saxagliptin and cardiovascular risk has been raised.…”
Section: Safety Of Saxagliptinmentioning
confidence: 95%